Growth of Copper Sulfate Pentahydrate Single Crystals by Slow Evaporation Technique - Bakr, Nabeel A.; Dhahir, Tariq A. Al-; Mohammad, Saja B. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Single crystals of CuSO4.5H2O (CSP) were grown by slow evaporation solution technique at room temperature from its aqueous solution with molarity (0.25, 0.5 and 1.5) M. The sizes of the crystals were up to (39×12×3) mm3, (33.05×30.5×4.7) mm3 and (19.12×15.3×5.5) mm3 respectively. XRD patterns were recorded for powder of single crystals to find the parameters of crystals. FTIR studies confirm the presence of various functional groups in the crystals. The optical absorption was study by using UV-Vis analysis. The spectra show low absorbance in the range between 300 nm and 550 nm. Energy gap (Eg) of crystals was found to be (4.17, 4.19 and 4.25) eV at the molarity of (0.25, 0.5 and 1.5) M respectively.